2002
DOI: 10.1115/1.1459078
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mixing Volumes in Serial Transport in Pipelines

Abstract: This paper presents a model for predicting the contaminated mixing volume arising in pipeline batch transfers without physical separators. The proposed technique represents an improvement over the existing methods since it takes into account time-dependent flow rates and accurate concentration-varying axial dispersion coefficients. The governing equation of the model forms a nonlinear boundary-value problem that is solved by a finite element method coupled to the Newton’s method. A comparison among the theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…The governing equation of the model is a nonlinear boundary value problem, which is solved by coupling the finite element method with Newton method. Rachid et al [14,15] proposed a new mixing calculation model. They found that the flow direction had no effect on the mixing volume with the same change in pipe diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The governing equation of the model is a nonlinear boundary value problem, which is solved by coupling the finite element method with Newton method. Rachid et al [14,15] proposed a new mixing calculation model. They found that the flow direction had no effect on the mixing volume with the same change in pipe diameter.…”
Section: Introductionmentioning
confidence: 99%
“…As a motivation for this study, there is the characterization of the interface contamination formed between batch transfers of two different fluids and its spread along the flow. Petroleum transport through long pipelines is an example of application for that (Rachid et al, 2002). The bulk properties were considered constant, the constitutive equations for a Carreau fluid were employed (Eq.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…This kind of phenomenon finds application in many subjects in engineering. In petroleum engineering, modeling and simulation of mixture volumes that arise between batch transfers of petroleum fractions in multiproduct pipelines has been studied by Rachid et al (2002). In environmental engineering, problems of liquid effluent dispersion in lakes and rivers are common.…”
Section: Introductionmentioning
confidence: 99%
“…The governing equation of the model is a nonlinear boundary value problem, which is solved by coupling the finite element method with Newton method. Rachid et al [14,15] proposed a new mixing calculation model. They found that the flow direction had no effect on the mixing volume with the same change in pipe diameter.The above research shows that the viscosity difference is the main factor that causes the tail of contamination, but these studies do not consider the special situations,such as dead-legs in a valve chamber, and are not closely integrated with practical engineering.…”
Section: Introductionmentioning
confidence: 99%